Impact of chemoreduction for conservative therapy for retinoblastoma in Argentina - Chantada, Guillermo Luis (2014)
BACKGROUND: Few studies were reported from developing countries regarding patient outcome and ocular survival in children with bilateral retinoblastoma treated with chemoreduction compared to external beam radiotherapy (EBRT). PROCEDURE: We undertook a retrospective study of three treatment eras: (1) (1988-1995) n = 68 when EBRT was used as primary conservative therapy; (2) (1995-2003) n = 46 when carboplatin-based systemic chemoreduction was introduced and (3) (2003-2009) (n = 83) when additional periocular chemotherapy was added for advanced tumors and pre-enucleation chemotherapy was given for those with massive buphthalmia. RESULTS: The probability of 5-year disease-free survival was 0.94 (95% confidence interval [CI] 0.91-0.98%) without significant differences among the three eras. Chemoreduction reduced the use of EBRT from 84.6% to 68.7% in eras 1 and 3, respectively (P = 0.008), which was more evident in cases with less advanced disease. Chemoreduction also significantly improved the 5-year probability of preservation of eyes with advanced disease from 0.13 (95% CI 0.04-0.27) during era 1 to 0.49 (95% CI 0.34-0.62) in era 3 (P < 0.0001). Chemoreduction was not associated with changes in the probability of extraocular relapse, which was reduced after the introduction of pre-enucleation chemotherapy. Second malignancies occurred in nine cases, acute myeloid leukemia being the most fatal one. Trilateral retinoblastoma occurred in three cases and all of them had been exposed to chemotherapy. CONCLUSIONS: Chemoreduction reduced the need for EBRT in eyes with less advanced disease and improved the preservation of eyes with advanced disease while its effects on secondary malignancies or trilateral disease remain unclear.